Terahertz Technology - You, Borwen; Lu, Ja-Yu (IntechOpen, 2022)
Electromagnetic waves within a terahertz frequency range are becoming critical to investigating molecules, materials, and possible applications that are operated by both visible light and infrared rays. This book discusses sensing, imaging, and optoelectronic technologies of terahertz electromagnetic waves in theory and experiments. Most terahertz technologies can be explained by fundamentals of applied physics that have been demonstrated in other spectral ranges. However, the optoelectronic technology and corresponding configurations of imaging and sensing techniques are so special for various terahertz material polarization waves, which are excited in solid-state media by high-peak power lasers and waveguide transportation. Thus, this book also specifies terahertz parameters and available technologies.